GAYA KEPEMIMPINAN PARTISIPASIF KEPALA SEKOLAH DALAM MENINGKATKAN KARAKTER SISWA DI SMKN 2 SIGLI KABUPATEN PIDIE - Junita Junita; Marwan Marwan; Munawar Munawar (Universitas Islam Negeri Sumatera Utara Medan, 2025)
The objectives of this study are: to identify the implementation of the principal?s participative leadership style in the context of secondary education, particularly in fostering students? character; to determine the influence of the principal?s participative leadership on work motivation, performance, and innovation within the school environment; and to examine the relationship between the principal?s participative leadership and the development of character-building programs for students in secondary schools. This research is field research (field study) with a qualitative approach. The study was conducted at SMKN 2 Sigli, a public vocational high school established on 9 November 1966 under the original name Sekolah Teknik Menengah (STM) Sigli. The subjects of this study are the principal and educators, consisting of 1 principal, 1 vice principal for student affairs, 1 guidance and counselling (BK) teacher, and 7 teachers. Data were collected through interviews, observation, and documentation, while data analysis employed the criteria of credibility, transferability, dependability, and confirmability. The results show that the implementation of a participative leadership style by the principal of SMKN 2 Sigli demonstrates a high level of effectiveness in creating a healthy and collaborative work environment. Supporting and inhibiting factors in the implementation of participative leadership in fostering students? character include, first, a major supporting factor in the form of the principal?s strong commitment to character development, reflected in exemplary attitudes, openness in communication, and the active involvement of teachers, students, parents, and external parties. The efforts made by the principal to optimise the leadership role in shaping students? character are reflected in the implementation of character-building strategies that embody a visionary, participative, and sustainable leadership approach..